2020
DOI: 10.3390/ijerph17197211
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Six Key Risk Behaviors for Chronic Disease among Adolescent Females

Abstract: Chronic diseases are the leading cause of disability and mortality globally. In Australia, females are at heightened risk. This research explored the prevalence, patterns, and correlates of six key risk behaviors (physical inactivity, poor diet, recreational screen time, inadequate sleep, alcohol use, and smoking) among adolescent females and whether knowledge of health guidelines was associated with adherence. Adolescent females completed an anonymous online questionnaire (N = 687; Mage = 13.82). Logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 35 publications
4
19
2
Order By: Relevance
“…In the present study, those behaviors were not important for clustering among girls. This finding was consistent with the Australian study identifying that alcohol consumption and smoking were not found to be essential factors for clustering among female adolescents [ 28 ]. Alcohol consumption and tobacco use are well-known as influential factors for various health problems, including cardiovascular diseases, cancers, liver disease, and lung disease [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, those behaviors were not important for clustering among girls. This finding was consistent with the Australian study identifying that alcohol consumption and smoking were not found to be essential factors for clustering among female adolescents [ 28 ]. Alcohol consumption and tobacco use are well-known as influential factors for various health problems, including cardiovascular diseases, cancers, liver disease, and lung disease [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…The finding that about half of each gender group were classified as adolescents who had healthy behaviors is consistent with the findings from the study of adolescents in Australia [ 23 , 28 ]. However, in the United States, the highest proportion of male adolescents were classified as having unhealthy behaviors, while the mixed group had the highest proportion of female adolescents, based on data from Add Health in 1994 (Wave I) and 2008 (Wave IV) [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Modifiable behavioural health risk factors such as smoking tobacco, inadequate fruit consumption, inadequate vegetable intake, risky alcohol consumption, physical inactivity and obesity have consistently been found to be associated with increased risk of NCDs and mortality from such diseases [ 2 , 3 , 4 , 5 ]. Often, these health risk factors can co-occur or cluster with psychological distress such as depression and anxiety [ 6 , 7 , 8 , 9 ]. Co-occurrence of health risk factors refers to concurrent engagement in two or more health risk factors and clustering refers to the association between co-occurring health risk factors [ 10 ].…”
Section: Introductionmentioning
confidence: 99%